A Peer and Volunteer Program for Patients and Their Families in the Pediatric Intensive Care Unit: A Pilot Program Evaluation - Pereira, Nichole; MacDonald, Christine; Drobot, Ashley; Bennett, Alexandra; Ali, Al-Bakir; Garros, Daniel (Frontiers in Pediatrics, 2021)
Introduction: Patients in the pediatric intensive care unit (PICU) are at risk of developing long-term morbidities following recovery from their critical illness. One such health outcome is called post-intensive care syndrome (PICS). PICS in pediatrics may be mitigated by interventions that facilitate adjustment to the PICU setting. Methods: The PICU implemented a two-pronged Peer and Volunteer (P/V) Program to help: (a) families adjust to the PICU experience with the support of a peer mentor (PM); and (b) patients receive non-medical interaction from trained volunteers (V). We designed a mixed-methods program evaluation targeting perspectives and feedback from PICU families and healthcare professionals (HCPs). Results: All stakeholder groups agreed that the PICU P/V Program was a valuable resource for PICU patients and their families. HCPs reported that they lack both time and training to provide regular developmental care to patients. However, the P/V Program may influence both families’ and HCP’s confidence in their ability to offer non-medical interaction to children in the PICU. Discussion: Important initial and on-going strengths and barriers to successful implementation were identified, including the need to clarify roles and intervention scope. The program evaluation served as a change management strategy and also helped to identify both areas for improvement and strategies for on-going sustainability. HCP’s exposure to the program and modelling by PMs may have helped HCPs to feel that it is within their job description and capacity to provide emotional support and guidance to families.